Immigration and population. - Bohon, Stephanie (Immigration and society., 2015)
Immigration is the primary cause of population change in developed countries and a major component of population change in many developing countries. This clear and perceptive text discusses how immigration impacts population size, composition, and distribution. The authors address major socio-political issues of immigration through the lens of demography, bringing demographic insights to bear on a number of pressing questions currently discussed in the media, such as: Does immigration stimulate the economy? Do immigrants put an excessive strain on health care systems? How does the racial and ethnic composition of immigrants challenge what it means to be American (or French or German)? By systematically exploring demographic topics such as fertility, health, education, and age and sex structures, the book provides students of immigration with a broader understanding of the impact of immigration on populations and offers new ways to think about immigration and society -- Présentation de l'éditeur.